Elderly care who live in mountainous areas: nursing professional’s knowledge importance - Dayamí Guerra Villalpanda; Eneida Bravo Polanco; Raquel Rubio Rojas (Medisur)
Nursing care must be approached from a holistic perspective that allows covering the patients’ real needs in their environment. One of the functions of the nurse is to help the sick or healthy elderly person to carry out the activities that contribute to their health, recovery or a peaceful death in the community. This article aims to reflect on the role that nurses play in caring for the elderly who live in mountainous areas and the importance of increasing these professionals’ knowledge of in this regard.